The second heart sound in ventricular septal defect - Saraçlar, Muhsin (The Turkish Journal of Pediatrics, 1972)
In order to investigate the diagnostic value of the second heart sound in patients with VSD, classified in groups, in regard to the hemodynamic findings and Gasul’s physiological standards a particular method was used, and with this method 42 cases were studied. The intervals between the closure of the aortic and pulmonic semilunar valves were measured. The conclusions obtained are as follows. The average of A_2-P_2 in the first group and the control group in the expiration could not be used for differentiation betOn the other hand the A_2-P_2 values in the expiration were found to be very useful in differentiation between the first and second groups. The second sound in the second group showed wide splitting in comparison with other groups. The average of A_2-P_2 in the second and Group 3-A in the expiration could not be used for differentiation between these groups.ween these groups.